Jezus – Ewangelizator [Ὁ Ἰησοῦς] κηρύσσων καὶ εὐαγγελιζόμενος τὴν βασιλείαν τοῦ θεοῦ (Łk 8,1) - Pisarek, Stanisław (Śląskie Studia Historyczno-Teologiczne, 1998)
The article is the 19th of the series on Jesus Titles which had been published in „Goœæ Niedzielny” weekly magazine since 1994–1996. The previous ones were a popular presentation of the New Testament Christology whilst the 19s article is a scientifically approached summary of the series. It was specially written for the Commemoration Book dedicated to Petr Pokorný who is professor in biblistics at the Department of Protestant Theology at Charles University in Prague (the Czech Republic) to celebrate his 65th birthday in 1998. As the title Jesus – the Evangelizer has not been used in the Bible (althhough it is used even in the Church’s official documents) the author puts forward the question – Is the title „Jesus Evangelizer” rooted in the Bible and what are its contents? This title has appeared recently with the new evangelization. John Paul II made a postulate in TMA: To discover Jesus Christ again as the only Redeemer of the world. The basis for it is a pericope about a rejection of Jesus Christ in Nazareth (Luke 4,16–30). From the philological point of view basing on BH, LXX and NT the line leeds from the Hebrew term me baœer (RAB:M) throng a Greek substantial form o( eu)aggelizo/menoj (LXX,NT) to the corresponding form evangelizer in medival Latin and the derived from this form neologisms in modern languages, especially in Roman languages up to its presence in Polish theological literature. Polish spelling is „evangelizator” (ewangelizator) but it can not be found in any dictionary of Polish. The author looked for this title in contemporary translations of the Bible and found a term „G³osiciel Ewangelii” (he who preaches the Gospel) as the closest and the most appropriate one. Analysis of the texts in NT where o( eu)aggelizo/menoj refers to Jesus showed topos of the verb eu)aggeli/zein in the New Testament; philological and exegetical analysis of the texts have been carried out and showed evidence that Jesus was in the function of a subject. The word eu)aggeli/zw/eu)aggeli/- zein is present in 55 places in the New Testament and it is also used 9 times in the context which refers to Jesus’s activities: Matt 11,5; Luke 3,14; 4,18; 4,43; 7,22; 8,1; 9,6; 16,16; 20,1. It is used as participium 20 times in the New Testament only in medial and passive form. The author presents the results of his own research and gives the definition: What is the definition of Jesus – Evangelizer? The most accurate and the shortest answer can be found in Luke 8,1 summarium: I)hsou=j diodeu/wn kata po/lin kai kw/mhn, khru/sswn kai eu)aggelizo/menoj th basilei/an tou= Qeou= which means Jesus constantly on his way (diodeu/wn) through towns and villages, proclaiming (khru/sswn) Good News about the Kingdom of God which has already come. This is what He was sent for. He himself is the Gospel (Mark 1,1). Basing on the original Greek text it is justfied to use the title I)hsou=j o( eu)aggelizo/menoj (the evangelizing Jesus) which can be translated into Latin used by the Church as Jesus Evangelizans, so the contemporary version of the title is Jesus – the Evangelizer. The author’s bibliography contains 32 items which were used as justification of the subject matter of this paper. Item no 27: Carlo Maria Martini, Głosiciel Ewangelii u św. Łukasza. Medytacje, WAM, Kraków 1993 (Duc in altum – wypłyń na głębię 9); Carlo Maria Martini, He who proclaims the Gospel in the Gospel according to Luke. Meditations, WAM, Cracow 1993 (Duc in altum – set out on deep waters 9).